Basis of Identification, Type of Syngenetic Assemblage, and Pattern of Development of Coal and Oil Shale in the Tanshan Area of the Eastern Liupanshan Basin, China - Caixia Mu; Rui Yang; Lianfu Hai; Qinghai Xu; Jun Yang; Chao Mei (Energies)
The Yan’an Formation in the Liupanshan Basin hosts substantial coal and oil shale resources. However, coal and oil shale often exhibit different types of associated or syngenetic combinations, which makes it difficult to recognize coal and oil shales, and research on the patterns of development of coal and oil shales is lacking. In this study, field outcrop, core, logging, and analytical data are comprehensively utilized to describe the characteristics of coal and oil shale, classify their syngenetic combinations, and establish a developmental model. Analytical results from the Tanshan area reveal that coal exhibits a lower density and higher oil content than oil shale. Specifically, coal shows oil contents ranging from 7.22% to 13.10% and ash contents of 8.25–35.66%, whereas oil shale displays lower oil contents (3.88–6.98%) and significantly higher ash contents (42.28–80.79%). The oil and ash contents of both coal and oil shale in the Tanshan area show a negative correlation, though this correlation is significantly stronger in coal than in oil shale. In long-range gamma-ray and resistivity logs, coal exhibits substantially higher values compared to oil shale, whereas in density logs, oil shale shows greater values than coal. Acoustic time difference logging reveals marginally higher values for coal than for oil shale, though the difference is minimal. There are five combination types between coal and oil shale in this area. The oil shale formed in a warm, humid, highly reducing lacustrine environment within relatively deep-water bodies, while coal developed in swampy shallow-water environments; both derive organic matter from higher plants. Variations in depositional settings and environmental conditions resulted in five distinct combination types of coal and oil shale.